2021
DOI: 10.1101/2021.09.28.462081
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Natural statistics support a rational account of confidence biases

Abstract: Previous work has sought to understand decision confidence as a prediction of the probability that a decision will be correct, leading to debate over whether these predictions are optimal, and whether they rely on the same decision variable as decisions themselves. This work has generally relied on idealized, low-dimensional modeling frameworks, such as signal detection theory or Bayesian inference, leaving open the question of how decision confidence operates in the domain of high-dimensional, naturalistic st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 80 publications
1
16
0
Order By: Relevance
“…The present findings suggest that the observation of m-ratio ≥ 1 is not as unnatural as previously considered, alleviating the need to presuppose the existence of metacognitive inefficiency as a default hypothesis. In fact, there is no intrinsic reason within the realm of SDT that restricts m-ratio less than 1, and our previous studies have indeed demonstrated that the pattern of m-ratio ≥ 1 naturally emerges as a consequence of our metacognitive system being adapted to statistical structures of the world (see Miyoshi & Lau, 2020 ; Webb, Miyoshi, So, Rajananda, & Lau, 2021 ).…”
Section: Discussionmentioning
confidence: 96%
“…The present findings suggest that the observation of m-ratio ≥ 1 is not as unnatural as previously considered, alleviating the need to presuppose the existence of metacognitive inefficiency as a default hypothesis. In fact, there is no intrinsic reason within the realm of SDT that restricts m-ratio less than 1, and our previous studies have indeed demonstrated that the pattern of m-ratio ≥ 1 naturally emerges as a consequence of our metacognitive system being adapted to statistical structures of the world (see Miyoshi & Lau, 2020 ; Webb, Miyoshi, So, Rajananda, & Lau, 2021 ).…”
Section: Discussionmentioning
confidence: 96%
“…In general, the purpose of this article is not to make specific judgments about the merits of one particular model of metacognitive monitoring over another. Such arguments have been the focus of much debate in the metacognitive literature, and we point the interested reader to these works (Fleming & Daw, 2017; Khalvati et al, 2021; Rahnev et al, 2020; Shekhar & Rahnev, 2022; Webb et al, 2021; Yeung & Summerfield, 2012). Rather, the intention of this article is to probe the consequences of what it means to posses more complex forms of confidence, however they might arise, for metacognitive information search and control more generally.…”
mentioning
confidence: 99%
“…However, critically, such dissociations can also be explained in several other ways, such as by assuming that increasing both the signal and noise in a stimulus affects both the signal and variability in the internal evidence distributions. In fact, a recent study showed that high confidence for high-intensity stimuli is observed even in neural networks trained to take all evidence into account (Webb et al, 2021). Therefore, we suggest that empirical confidence-accuracy dissociations where high-intensity stimuli with matched d ′ produce higher confidence rating be renamed to “high-intensity–high-confidence” effect.…”
Section: Discussionmentioning
confidence: 99%